Clinical features of Epstein-Barr virus-associated infectious mononucleosis in hospitalized Korean children - Keun Hyung Son; Mee Yong Shin (Korean Pediatric Society, 2011)
PurposeFew studies have been conducted on the recent status of infectious mononucleosis (IM) in Korean children. The aim of this study was to evaluate the recent trend in the clinical manifestations of Epstein-Barr virus (EBV)-associated IM as well as the clinical differences according to age.MethodsA retrospective study was performed on 81 children hospitalized with EBV-associated IM who fulfilled the serological criteria for the diagnosis of EBV infection (viral capsid antigen immunoglobulin M positive). The patients were divided into 3 age groups: <5 years, 5 to 9 years, and ≥10 years. We evaluated the recent trend in clinical manifestations and the differences in clinical and laboratory findings among the 3 age groups.ResultsThirty (37%) children were under 5 years of age, 38 (46.9%) were 5 to 9 years of age, and 13 (16%) were 10 years of age or older. The differences in the symptoms and signs among the 3 age groups were not statistically significant, except for headache. The mean duration of fever was 7.7 days (range, 0 to 18 days). A comparison of liver enzyme elevation among the age groups showed an association with advancing age (26.6%, 63.1%, and 76.9%, respectively, P=0.04)ConclusionThis study showed that EBV-associated IM in Korean children continues to occur mostly in children under 10 years of age. In children with EBV-associated IM, the incidence of headache and liver enzyme elevation, the duration of fever, and the proportion of females to males were all positively associated with advancing age.